2021
DOI: 10.1186/s12864-021-07542-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation of microRNA expression in the human placenta driven by population identity and sex of the newborn

Abstract: Background Analysis of lymphocyte cell lines revealed substantial differences in the expression of mRNA and microRNA (miRNA) among human populations. The extent of such population-associated differences in actual human tissues remains largely unexplored. The placenta is one of the few solid human tissues that can be collected in substantial numbers in a controlled manner, enabling quantitative analysis of transient biomolecules such as RNA transcripts. Here, we analyzed microRNA (miRNA) express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The influence of maternal environment on placental function is well documented from conception to birth and epigenetic mechanisms, i.e., DNA methylation and regulation by microRNAs seem to be a major contributor. These mechanisms add another level to the sexual dimorphism of the human placenta as they are also modulated by fetal sex [ 140 , 141 , 142 ].…”
Section: Hormonal and Molecular Causes Underlying Fetal And Placental Sexual Dimorphismsmentioning
confidence: 99%
“…The influence of maternal environment on placental function is well documented from conception to birth and epigenetic mechanisms, i.e., DNA methylation and regulation by microRNAs seem to be a major contributor. These mechanisms add another level to the sexual dimorphism of the human placenta as they are also modulated by fetal sex [ 140 , 141 , 142 ].…”
Section: Hormonal and Molecular Causes Underlying Fetal And Placental Sexual Dimorphismsmentioning
confidence: 99%
“…MiRNA have emerged as new frontier in the study of placenta sex, with two recent studies on term placenta reporting differences in miRNA expression in male and female term placenta. Guo et al [ 97 ] found 32 miRNA differentially expressed, with the male-selective transcripts annotated as evolutionarily younger and enriched in endocrine functions, and female selective transcripts enriched for the imprinted miR-379 cluster on Chr14 (C14MC) which linked to estradiol, glucocorticoids, and brain-specific mRNA targets. In their study of the interaction of placental sex and maternal n-3 LCPUFA dietary supplementation, Sedlmeier et al [ 72 ] highlighted miR-99a as differentially expressed by sex and modulated by maternal diet, linking its expression to sex differences in mTOR-related mRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inhibition of systemXc-, GSH depletion, and GPX4 inactivation become the key links in inducing ferroptosis in cells. The placenta plays a key role in fetal development, maternal–fetal communication, maternal homeostasis, and pregnancy adaptation to injuries ( Liang et al, 2018 ; Hao et al, 2020 ; Guo et al, 2021 ). It is generally known that early pregnancy disruptions in placentation and placental function leads to insufficient spiral artery remodeling and, as a result, prolonged placental ischemia ( Shao et al, 2017 ; Kelemu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%